Pandemic H1N1 influenza A viruses suppress immunogenic RIPK3-driven dendritic cell death. Issue 1 (December 2017) - Hartmann, Boris; Albrecht, Randy; Zaslavsky, Elena; Nudelman, German; Pincas, Hanna; Marjanovic, Nada; Schotsaert, Michael; Martínez-Romero, Carles; Fenutria, Rafael; Ingram, Justin; Ramos, Irene; Fernandez-Sesma, Ana; et al.
Abstract The risk of emerging pandemic influenza A viruses (IAVs) that approach the devastating 1918 strain motivates finding strain-specific host–pathogen mechanisms. During infection, dendritic cells (DC) mature into antigen-presenting cells that activate T cells, linking innate to adaptive immunity. DC infection with seasonal IAVs, but not with the 1918 and 2009 pandemic strains, induces global RNA degradation. Here, we show that DC infection with seasonal IAV causes immunogenic RIPK3-mediated cell death. Pandemic IAV suppresses this immunogenic DC cell death. Only DC infected with seasonal IAV, but not with pandemic IAV, enhance maturation of uninfected DC and T cell proliferation. In vivo, circulating T cell levels are reduced after pandemic, but not seasonal, IAV infection. Using recombinant viruses, we identify the HA genomic segment as the mediator of cell death inhibition. These results show how pandemic influenza viruses subvert the immune response. The differences in virus-host interactions resulting in distinct pathogenicity of seasonal and pandemic influenza A viruses (IAV) are not well understood. Here, the authors show that the hemagglutinin segment from pandemic, but not seasonal, IAV suppresses RIPK3-mediated dendritic cell death, thereby reducing T cell activation.